(3LgI GdhMOI GdeJYbdI Ydi GdafGQjs - (3GdTQhGfj, eMeO Cejf Hf UOQ GdOjf, J (B1036 (3g``s
(3ChdgG (B:s
(3Ef CMSf eG jaJM Hg GdefWb hGdcdGe MeO Gddg GdhGMO GdPj HQF GdCfGe (B... (3agPg JMbjbGJ TQjaYI HYHGQI DGFbI JSGHb eYGfjgG GdCPgGf Hd JObjbGJ ZGeVI JYLH GSJeGYgG GdBPGf Ydi GdeHMK s
(3BNQgG (B:s
... (3hHjGf GdeQGO ef GdYHGQGJ GdVjbI ggfG XgQ Cf eG ChQOg HYV ef JUOi dTQM GdcJGH aHYjO Yf GdMb hefMQa Yf SeJ GdUhGH hCf CbQH eG PcQfG JGQI dcfg HYjO Yf CNQi JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\41s
(3NdGUI GdCKQ aj CYjGf GdbQf GdMGOj YTQ deMeO Cejf GdMehj (B3\476s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs